2019
DOI: 10.17756/jocd.2019-024
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of “Classic” 3:1 Ketogenic Diet Complete Meal Replacement Treatment of Obesity-Related Type 2 Diabetes

Abstract: Introduction: Low carbohydrate (CH) diets have been used in the management of obesity-related T2DM, with modest results. "Classic" ketogenic diets (KD) used in epilepsy are very low CH (10-20 g/day), very high fat (87-90% of calories) diets. We report a pilot study of treatment of obesity-related T2DM with "classic" 3:1 [fat]:[carbohydrate + protein] weight ratio diet using the novel approach of a complete ready-made meal replacement program. Methods: In an open label study, T2DM patients with BMI ≥ 30 kg/m 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…It is evident that weight reduction helps to decrease insulin resistivity which will help in lowering of RBG level. It is found that hyperglycaemia is due to insulin resistivity so glucose level can be controlled by addressing this problem of insulin resistivity (Jackness et al, 2013;Klein et al, 2019).…”
Section: Effect On Fasting Blood Glucose Levelmentioning
confidence: 99%
“…It is evident that weight reduction helps to decrease insulin resistivity which will help in lowering of RBG level. It is found that hyperglycaemia is due to insulin resistivity so glucose level can be controlled by addressing this problem of insulin resistivity (Jackness et al, 2013;Klein et al, 2019).…”
Section: Effect On Fasting Blood Glucose Levelmentioning
confidence: 99%